LC-HRMS profiling, antibacterial activities, and in silico study of ethyl acetate extract from Dracaena angustifolia root bark - I WAYAN KARTA; WARSITO WARSITO; MASRURI MASRURI; I WAYAN MUDIANTA (Society for Indonesian Biodiversity, 2024)
Abstract. Karta IW, Warsito W, Masruri M, Mudianta IW. 2024. LC-HRMS profiling, antibacterial activities, and in silico study of ethyl acetate extract from Dracaena angustifolia root bark. Biodiversitas 25: 3555-3567. The escalating resistance of bacteria to conventional antibiotics has spurred new sources of exploration of natural antibacterial agents. This study aimed to unveil the antibacterial potential of Dracaena angustifolia Roxb. root bark extract through a comprehensive approach of in vitro assays, LC-HRMS analysis, in silico, and molecular dynamics simulations. The root bark, extracted with ethyl acetate, was identified using LC-HRMS and tested for antibacterial activity using the diffusion method. The extract demonstrated the ability to inhibit the growth of Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Salmonella typhi. Of 37 annotated compounds, four (Arbutin, (-)-Caryophyllene oxide, Ruscoponticoside C, and Striatisporolide A) were predicted by PASS to exhibit antibacterial potential. Molecular docking revealed differences in the binding interactions between amino acid residues and ligands of the target protein (PDB ID: 3HUN). Ruscoponticoside C shares binding site similarities with the native ligand Ampicillioic acid. Molecular dynamics simulations showed that the ligand-protein complexes of Arbutin, Ruscoponticoside C, Striatisporolide A, and Ampicillioic acid were more stable compared to Chloramphenicol. This study suggests that this plant’s root bark extract has potential as an antibacterial agent, inspiring further in-depth research into the isolation of its secondary metabolites and their potential impact on drug discovery.